Journey Towards a Family Lay Spirituality: A Memoir - Emiliano T. Hudtohan (International Journal of Management and Education in Human Development, 2022)
My spiritual journey started with my maternal grandmother, Lola Tesang. She trained me to pray the rosary, go to confession on a Saturday and attend mass on a Sunday. Her devotion to the Holy Family motivated me to be a good grandson to qualify as Boy Jesus on the Feast of St. Joseph. My Lasallian spirituality was formed in my years of education with the brothers from Grade School, High School, college up to my doctoral degree; I was immersed in Lasallian spirituality for 17 years as a La Salle Brother. I gained a parish-based spirituality as a lay minister and Vice President of Our Lady of the Assumption Pastoral Council. I had a faith renewal experience as member of a Charismatic Bukas Loob sa Diyos Movement, where I received a gift of healing. My doctoral dissertation led me to explore quantum healing and quantum theology, which provided me an expansive understanding of humanity in three dimensions: physical, metaphysical and spiritual life. My encounter with Elsie Rabago inspired me to make a full spiritual circle from an anthropocentric God (Father, Son and Holy) to a quantum God of Pure Energy and a return to a human relationship with God in the Person of Jesus, the Beloved and the Blessed Virgin Mary as Mama Mary.